Representation of Nature of Science in Pre-service Teacher Education Programme - Singhal, Mamta (JOURNAL OF INDIAN EDUCATION, 2017)
Science education holds a prominent place in our education system. The fact that the Constitution stresses on developing scientific temper as one of the fundamental duties of Indian citizens speaks of the high value attached to science education in our country. While earlier curricular reforms and policies have emphasised on the ‘product’ or ‘process’ approach in science, the recent reforms have paid attention to the epistemological aspects of science. This paper examines the pre-service teacher education curricula (B.Ed.) of three universities for their focus on the Nature of Science.